Cryogenic bath-type heat exchangers for ultra-pure noble gas applications. (1st May 2022) - Murra, M.; Schulte, D.; Cristescu, I.; Disdier, J.-M.; Huhmann, C.; Tatananni, D.; Weinheimer, C.
Abstract: Two cryogenic bath-type heat exchangers for ultra-pure noble gas applications were developed with particular emphasis on noble gas liquefaction in cryogenic distillation systems. The main objective was to construct heat exchangers for xenon from materials that do not emanate radon and that fulfill ultra-high vacuum standards. Therefore, only high-quality copper and stainless steel materials were used. Especially, large-area oxygen-free copper fins with high conductivity in a new design ensure efficient heat transfer. One bath-type Xe-Xe heat exchanger was designed with a diameter of 50 cm to achieve a xenon condensing capacity of at least 100 kg/h. In order to guarantee the necessary heat transfer between the two xenon reservoirs, this heat exchanger features a specially manufactured stainless steel flange with a copper plate welded inside. We first tested our concept on a dedicated bath-type heat exchanger with a reduced diameter of 30 cm using liquid nitrogen to liquefy the xenon. A model based on conservative assumptions such as film boiling on the nitrogen side and film condensation on the xenon side was developed and applied to caluclate the expected heat transfer for our design. We were able to demonstrate an adjustable xenon liquefaction rate of up to 113 kg/h limited only by our measurement procedure at a cooling efficiency of (0.98 ± 0.03) for the LN2 -Xe heat exchanger.